Toba Batak Ethnomedicine in Sipituhuta Village, Pollung District, Humbang Hasundutan Regency, North Sumatra - Jamilah Nasution; Maisarah Lumban Gaol; Riyanto Riyanto; Ferdinand Susilo (Journal of Tropical Ethnobiology, 2023)
The importance of introducing medicinal plants of Toba Batak tribe as traditional medicinal ingredients increases public knowledge about their use in general. The objective of this study was to find out the types of plants that have medicinal properties and how they were used by the Toba Batak tribe. The types of research used were descriptive qualitative and quantitative with structured interview methods directly to predetermined informants. The selection of informants was carried out using a purposive sampling method, with a total of 9 informants. Based on the results, there are 90 species and 46 families of plants that have potential as medicine. Based on family, the number of species most widely used by the people of Sipituhuta Village are Zingiberaceae (7 species), Asteraceae (6 species), Poaceae (6 species) and Solanaceae (5 species).